1988
DOI: 10.1007/bf00004908
|View full text |Cite
|
Sign up to set email alerts
|

The nature and role of learning in the orientation and migratory behavior of fishes

Abstract: SynopsisFish migration may be viewed as the product of two processes; the selection and tracking of optimal environmental conditions through time and space, and the use of predictive information about environmental structure to bias movements towards a goal. The establishment and maintenance of directional bias is based on the interaction of experience and instinct. The preoccupation of much fish orientation research with innate fixed patterns of behavior on one hand and hydrodynamics on the other has led us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 64 publications
3
94
0
Order By: Relevance
“…For example, smolt actively swam against inflowing currents but did not actively swim against outflowing currents; smolt swam strongly against a positive salinity gradient but did not reverse their behaviour when there was a negative salinity gradient. These observations are consistent with the hypothesis that smolt exploit an innate compass to maintain a preferred bearing (reviewed in Dodson 1988). …”
Section: Discussionsupporting
confidence: 89%
“…For example, smolt actively swam against inflowing currents but did not actively swim against outflowing currents; smolt swam strongly against a positive salinity gradient but did not reverse their behaviour when there was a negative salinity gradient. These observations are consistent with the hypothesis that smolt exploit an innate compass to maintain a preferred bearing (reviewed in Dodson 1988). …”
Section: Discussionsupporting
confidence: 89%
“…Aronson, 1951Aronson, , 1971Reese, 1989;Teyke, 1989). This cognitive mechanism could be relevant for fish for traveling in their natural habitat, especially for species that are relatively site attached, such as goldfish and common carp (Reynolds, 1983), or for those that perform repeated migrations to different areas of their habitat (Dodson, 1988;Reese, 1989). Certainly, such a cognitive system would permit flexible and adaptive spatial behaviors, such as those observed here.…”
Section: Use Of Allocentric and Egocentric Strategies As Revealed By mentioning
confidence: 79%
“…Research in this field has been focused mainly on the innate fixed patterns of behavior and on sensory, ecological, and zoological factors. What seems to be underestimated in this research, though, is the possibility that spatial behavior is a flexible process that involves learning and memory mechanisms and cognitive phenomena (for a review, see Dodson, 1988). Such mechanisms are indicated by a number of naturalistic and experimental studies, such as the pioneer work of Aronson (1951Aronson ( , 1971) that showed that the gobiid fish Bathygobius soporator uses learned information about the spatial relationships of tide pools, or topographical memories acquired during exploration, to orient itself accurately.…”
mentioning
confidence: 99%
“…Specific populations of adult Atlantic cod have been characterised as resident, homing, or dispersing (Robichaud & Rose 2004, Neat et al 2006. Site fidelity or homing patterns can vary across life stages in response to increased opportunity for spatial or social learning, depending on habitat stability (Dodson 1988, Odling-Smee & Braithwaite 2003 or body condition (Comeau et al 2002). These varying patterns affect the contributions of movements of individual fishes to population connectivity.…”
Section: Introductionmentioning
confidence: 99%